2002
DOI: 10.1016/s1010-7940(02)00244-0
|View full text |Cite
|
Sign up to set email alerts
|

Sources of pathogens causing pleuropulmonary infections after lung cancer resection

Abstract: Our results indicate that pathogens that cause pleuropulmonary infective complications are probably acquired postoperatively from the patient's oral cavity, pharynx and hypopharynx. Appropriate antibiotic prophylaxis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 12 publications
3
24
0
3
Order By: Relevance
“…One study reports that pulmonary infection may impact negatively on the survival of lung cancer patients [3]. A thorough review of the literature indicated that bronchial colonisation has been often evaluated in patients undergoing a cancer resection, as this population has a high risk of severe pulmonary infectious complications and mortality following thoracic surgery [6,7,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…One study reports that pulmonary infection may impact negatively on the survival of lung cancer patients [3]. A thorough review of the literature indicated that bronchial colonisation has been often evaluated in patients undergoing a cancer resection, as this population has a high risk of severe pulmonary infectious complications and mortality following thoracic surgery [6,7,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with previous studies on PAC is difficult since the majority of data relates to patients with lung resection for cancer [22][23][24][25][26]. However, the majority of these studies on lung cancer demonstrate a significant correlation of PAC with postoperative lung infection as seen in this study on esophageal cancer [22,25,26].…”
Section: Discussionmentioning
confidence: 62%
“…-If the empyema is healed, the surgical procedure for lung cancer can be planned as normal -Decortication is not always necessary -Interval between the empyema treatment and the operation: -no strict recommendations -no suffi cient data for comparison -Post-operative adjuvant therapy should be used if required of post-operative sputum samples (p<0.01) [45]. These data, although useful, are of little help for pre-operative selection.…”
Section: Intrathoracic Contaminationmentioning
confidence: 99%